A New Era? A Case Study of the University of Manitoba’s Response to Federal International Student Policy - Tamtik, Merli; Desai Trilokekar, Roopa; Liu, Helen (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2026)
Canada’s federal and institutional policies have long been aligned to attract and retain international students and skilled immigrants. This policy landscape shifted dramatically in January 2024, when Immigration, Refugees and Citizenship Canada announced a national cap on study permits. This article examines the impact of these new federal policy measures on research-intensive universities. Specifically, it asks: (1) How did universities interpret and respond to these policy changes? and (2) How did they adapt organizationally? Drawing on institutional theory and a case of the University of Manitoba, we introduce the concept of crisis isomorphism to explain how universities may navigate abrupt policy disruptions. The study contributes to understanding the shifting terrain of internationalization in Canada amid heightened federal intervention.